2022
DOI: 10.1093/femsle/fnac042
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and antibiotic resistance of Shigella sonnei isolates

Abstract: Shigellosis is one of the most important gastric infections caused by different species of Shigella, and has been regarded as a serious threat to public health. Lineage/sublineage profile of Shigella sonnei is strongly associated with the antibiotic resistance and population structure of this pathogen. In this study, we determined the phylogeny and antibiotic resistance profiles of S. sonnei strains, isolated from 1246 stool and 580 food samples, using multiplex PCR–HRMA genotyping and Kirby–Bauer disk diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…S. flexneri and S. sonnei (non-Shiga-toxin producing strains) are mainly responsible for non-Dysenteriae disease (mild diarrhoea) caused by Shigella strains [5,8,16]. The pathogenesis of Shigella possesses unique and multiple well-established pathogenic mechanisms mediated by seven distinct steps, including attachment to the epithelial host cell, entry to the cell, host cell autophagy evasion, vacuole formation, vacuole rapture, intracellular life and immune response [44,45].…”
Section: Molecular Mechanisms Of Non-dysenteriae Shigella Species Pat...mentioning
confidence: 99%
See 2 more Smart Citations
“…S. flexneri and S. sonnei (non-Shiga-toxin producing strains) are mainly responsible for non-Dysenteriae disease (mild diarrhoea) caused by Shigella strains [5,8,16]. The pathogenesis of Shigella possesses unique and multiple well-established pathogenic mechanisms mediated by seven distinct steps, including attachment to the epithelial host cell, entry to the cell, host cell autophagy evasion, vacuole formation, vacuole rapture, intracellular life and immune response [44,45].…”
Section: Molecular Mechanisms Of Non-dysenteriae Shigella Species Pat...mentioning
confidence: 99%
“…dysenteriae is one of the four serological groups of Shigella bacteria. Type 1 of S. dysenteriae is the only bacterial strain of Shigella species considered as the clinical group of Dysenteriae Shigella species and differentiated from other species due to the production of Shiga toxins (Stxs); however, some studies recently reported the production of Stxs by S. sonnei isolated from clinical samples [8,74]. S. dysenteriae type 1 is also considered one of the leading causes of bacillary dysentery or shigellosis and is transmitted to humans through the ingestion of contaminated water or food.…”
Section: Dysenteriae Shigella Species Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lineage III has exhibited a higher level of success in terms of its global spread, accounting for most strains present in South America, Africa, and Asia [ 13 , 14 , 62 , 63 ]. One of key characteristics of lineage III is its higher accumulation of resistances to antibiotics, a fact that is key for its global expansion [ 55 , 64 ].…”
Section: Key Aspects In the Evolution Of S Higella ...mentioning
confidence: 99%
“…Therefore, there is a strong need for the surveillance and control of these strains [ 3 , 9 ]. Examining both the phenotypic and genotypic antimicrobial resistance profiles of Shigella is of utmost importance for accurately identifying appropriate antibiotics for the treatment of shigellosis, particularly given the ongoing alterations in resistance profiles [ 10 ]. Molecular typing techniques have been used with increasing frequency in studies of the epidemiology Shigella spp.…”
Section: Introductionmentioning
confidence: 99%